0
$\begingroup$

Let $(a_n)$ be a bounded sequence. Suppose that for every bounded sequence $(b_n)$ we have $\lim_{n\rightarrow\infty}\sup(a_n+b_n) = \lim_{n\rightarrow\infty}\sup a_n + \lim_{n\rightarrow\infty}\sup b_n$. Prove that $(a_n)$ is convergent.

We can take $b_n=-a_n$ to get $\lim_{n\rightarrow\infty}\sup a_n + \lim_{n\rightarrow\infty}\sup (-a_n) = 0$. For any subsequence of $a_n$ which converges to $L$, the corresponding subsequence of $-a_n$ converges to $-L$. How can we conclude from here?

$\endgroup$
2
$\begingroup$

Hint: $$\lim_{n\to\infty}\sup (-a_n)=-\lim_{n\to\infty}\inf a_n.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.